2012
DOI: 10.1007/s00268-012-1504-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Necrotizing Pancreatitis: Redefining the Role of Surgery

Abstract: A highly conservative approach avoiding open necrosectomy in NP results in significantly lower mortality than previous serial FNA and consecutive indication for surgery in case of proven infection. Open surgery in NP should be reserved for concomitant intra-abdominal complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Another study showed that pancreatic necrosis was associated with higher morbidity and mortality rates. 20 In this study, we found that pancreatic necrosis was associated with higher mortality, and pancreatic necrosis .50% was an independent prognostic factor of survival in patients with SAP.…”
Section: Discussionmentioning
confidence: 53%
“…Another study showed that pancreatic necrosis was associated with higher morbidity and mortality rates. 20 In this study, we found that pancreatic necrosis was associated with higher mortality, and pancreatic necrosis .50% was an independent prognostic factor of survival in patients with SAP.…”
Section: Discussionmentioning
confidence: 53%
“…As direct diagnostic methods for infectious necrotizing pancreatitis, CT or US guided FNA can be used for bacteriological examination . In the past, the routine use of FNA was recommended when infectious necrotizing pancreatitis was suspected, but this indication has become more limited recently .…”
Section: Resultsmentioning
confidence: 99%
“…Pancreatic necrosis, associated with septic conditions, determines the production of so-called infected pancreatic necrosis (IPN), a leading cause of death (Khanna et al, 2013) which can yield figures of 45% (Alsfasser et al, 2012).…”
Section: Introductionmentioning
confidence: 99%